Noelin1 Affects Lateral Mobility of Synaptic AMPA Receptors - Pandya, Nikhil J.; Seeger, Christian; Babai, Norbert; Gonzalez-Lozano, Miguel A.; Mack, Volker; Lodder, Johannes C.; Gouwenberg, Yvonne; Mansvelder, Huibert D.; Danielson, U. Helena; Li, Ka Wan; Heine, Martin; Spijker, Sabine; et al. (Cell Reports, 2018)
Lateral diffusion on the neuronal plasma membrane of the AMPA-type glutamate receptor (AMPAR) serves an important role in synaptic plasticity. We investigated the role of the secreted glycoprotein Noelin1 (Olfactomedin-1 or Pancortin) in AMPAR lateral mobility and its dependence on the extracellular matrix (ECM). We found that Noelin1 interacts with the AMPAR with high affinity, however, without affecting rise- and decay time and desensitization properties. Noelin1 co-localizes with synaptic and extra-synaptic AMPARs and is expressed at synapses in an activity-dependent manner. Single-particle tracking shows that Noelin1 reduces lateral mobility of both synaptic and extra-synaptic GluA1-containing receptors and affects short-term plasticity. While the ECM does not constrain the synaptic pool of AMPARs and acts only extrasynaptically, Noelin1 contributes to synaptic potentiation by limiting AMPAR mobility at synaptic sites. This is the first evidence for the role of a secreted AMPAR-interacting protein on mobility of GluA1-containing receptors and synaptic plasticity. Pandya et al. find that the secreted protein Noelin1 binds AMPA-type glutamate receptors with high affinity. They show a role in limiting receptor mobility and keeping receptors at synaptic sites in a subunit-specific way. This is the first evidence for a secreted auxiliary subunit in mobility and plasticity of glutamate receptors.
CRIS-Team Scopus Importer:2022-08-05
Keywords: AMPAR-associated protein; glutamate receptor; receptor mobility; synapse function; synaptic plasticity